Readiness to treat and factors associated with survival of newborns with breathing difficulties in Ethiopia - Wasihun Andualem Gobezie; Patricia Bailey; Emily Keyes; Ana Lorena Ruano; Habtamu Teklie (BMC, 2019)
Abstract Background Ethiopia is one of five countries that account for half of the world's 2.6 million newborn deaths. A quarter of neonatal deaths in Ethiopia are caused by birth asphyxia. Understanding different dimensions of the quality of care for newborns with breathing difficulties can lead to improving service provision environments and practice. We describe facility readiness to treat newborns with breathing difficulties, the extent to which newborn resuscitation is provided, and by modeling the survival of newborns with difficulties breathing, we identify key factors that suggest how mortality from asphyxia can be reduced. Methods We carried out a secondary analysis of the 2016 Ethiopia Emergency Obstetric and Newborn Care Assessment that included 3804 facilities providing childbirth services and 2433 chart reviews of babies born with difficulties breathing. We used descriptive statistics to assess health facilities' readiness to treat these newborns and a binary logistic regression to identify factors associated with survival. Results Over one-quarter of facilities did not have small-sized masks (size 0 or 1) to complete the resuscitation kits. Among the 2190 cases with known survival status, 49% died before discharge, and among 1035 cases with better data quality, 29% died. The odds of surviving birth asphyxia after resuscitation increased eightfold compared to newborns not resuscitated. Other predictors for survival were the availability of a newborn corner, born at term or post-term, normal birth weight (≥2500 g) and delivered by cesarean or assisted vaginal delivery. Conclusion The survival status of newborns with birth asphyxia was low, particularly in the primary care facilities that lacked the required resuscitation pack. Newborns born in a facility with better data quality were more likely to survive than those born in facilities with poor data quality. Equipping health centers/clinics with resuscitation packs and reducing the incidence of preterm and low birth weight babies should improve survival rates.